PROFILE OF CHARACTERISTIC, RISK FACTOR, AND STROKE SEVERITY ON INFARCTION STROKE PATIENTS - Aisyah Rizki Ramadhani; Mohammad Saiful Ardhi; Subur Prajitno (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2022)
Background: Stroke is the second leading cause of death and the third leading cause of morbidity. Therefore, it is important to know which risk factor that most patients have. Stroke can be divided according to its severity using NIHSS, NIHSS itself has strong ability to predict outcomes after stroke Objective: This study’s aim to learn about profile of characteristic, risk factor, and stroke severity on infarction stroke patients in ward Seruni A RSUD Dr. Soetomo from July 2018 – June 2019. Methods: This descriptive observational study’s samples are patients with infarction stroke in ward Seruni A RSUD Dr. Soetomo from July 2018 – June 2019. The observed profile include age, sex, ethnic, family history of vascular disease, history of hypertension, diabetes, heart disease, dyslipidemia, obesity, smoking, alcohol consumption, physical inactivity, and stroke severity. Results: From 200 patiens, 55% (110) are 56-70 years old. 61% (122) patients are male. 81 out of 96 are Javanese. 25 out of 135 have family history of vascular disease, 140 out of 194 have hypertension, 69 out of 190 have diabetes, 27 out of 183 have heart disease, 101 out of 174 have dyslipidemia, 62 out of 162 have obesity, 33 out of 82 smoke, 4 out of 63 consume alcohol, and 50 out of 55 are inactive physically. On admission, out of 60 patients, 27 have moderate stroke, 25 minor, and 8 moderate to severe. On discharge, out of 49 patients, 23 have moderate stroke, 20 minor, 3 moderate to severe, and 3 severe. Conclusion: Infarction stroke patients were mostly male and the peak incidence occur between 56-70 years old. Most patients have histories of hypertension, dyslipidemia, and diabetes. On admission and discharge, most patients have moderate stroke, followed by mild stroke.